Genomics in upper tract urothelial carcinoma. Issue 1 (January 2017) - Kammerer-Jacquet, Solene-Florence; Mathieu, Romain; Peyronnet, Benoit; Rioux-Leclercq, Nathalie; Bensalah, Karim
Abstract : Purpose of review: Upper tract urothelial carcinoma (UTUC) is a relatively rare and poorly investigated disease. The objective of this review was to discuss recent advances in genomics and their implication regarding prognosis and treatment. Recent findings: UTUC were compared with urothelial carcinoma of the bladder (UCB) at genomic and transcriptomic levels. Molecular studies focused on identifying new prognostic biomarkers that were often initially described in UCB and extrapolated to UTUC. Some of them could be interesting to improve the management of UTUC. Summary: Recent studies improved our understanding of UTUC as a distinct entity compared with UCB. Although UTUC shares many of the same genomic alterations with UCB, some key differences have been identified as oncogenic drivers of these cancers. This better comprehension of genomics could lead to new prognostic markers that may refine UTUC treatment.